Desenvolvimento de protocolo psicológico de avaliação e acompanhamento ao surdo pré-lingual com indicação para o implante coclear - Maciel, Lesle (2017)
The deaf who has not developed any oral and / or signal language has not had access to assistance that introduces him to the sound world. The objective of this research is to develop a protocol of psychological assistance for the deep deaf subject who wishes to do the Cochlear Implantation procedure. Three records attended at a private hospital, from 2006 to 2009, were analyzed. A multiprofessional team (physicians, speech therapists and psychologist) was performed the medical services. Two patients were treated by the whole team and the third one was attended according to the standard protocol, being assisted by the physician and speech therapist. The criteria for selecting the medical records were: be diagnosed with severe or profound bilateral hearing loss neurosensory, prelingual with medical and phonoaudiological indication for Cochlear Implant procedures. The project was submitted and approved by the Research Ethics Committee, under number CAAE 68162017.0.0000.5482. The choice of data analysis was the Content Analysis. The results of psychological counseling in these profound pre-lingual deaf users did not meet the speech therapist criterion, but when listening to certain noises that were throughout the services symbolized and incorporated into the daily routine of their lives, dismissed of caregivers and / or companions. The recognition and symbolization of noise in sounds with meanings indicate the magnification of the subjectivity of these subjects. These results indicate guidelines for the creation of a psychological protocol that allows gains in the life quality of the subject who submits to the Cochlear Implant process, as well as autonomy and decrease in the dependence of third parties or caregivers